Migration remittances, poverty and inequality: The Philippines - Ernesto M. Pernia (University of the Philippines, School of Economics (UPSE), 2008)
The paper looks into the effects of international migration and remittances on household incomes and well-being, poverty reduction, human capital investment, saving, and regional development in the home country. Remittances appear to raise average incomes for all income groups but more so for the richer households than for the poorer ones, a finding that is consistent with that in several Latin American countries. Such eyeballing of the data is supported by econometric analysis which further reveals that remittances enhance household savings, spending on education and health care, and help the poor move out of poverty. Analysis at the regional level shows that, ceteris paribus, remittances also appear to contribute importantly to regional development, although overall increases in regional incomes do not seem to benefit low income households as much as the upper income ones.
Keywords: 330